A multi-functional converter based switched reluctance motor drive for electric vehicle - Dungrothu Kalpana; Malligunta Kiran Kumar; Pidikiti Tripura (Institute of Advanced Engineering and Science, 2022)
Owing to the resilience and ease of control, switched reluctance motors are commonly utilized in electric vehicle drives. This paper provides a topology for a multi-functional power converter for switched reluctance motor based electric vehicle drive with driving, braking and charging potentialities. With efficient control algorithms, a single power electronic converter is used for motoring, regenerative braking, and charging of the battery bank, resulting in a cost-effective power electronic interface. The front-end voltage control and current control of the switched reluctance motor (SRM) are used to achieve open loop and closed loop speed control during driving mode. Re-generation is made possible through restricted switching of phases in negative torque region. A bridgeless rectifier converter is built in battery charging mode by combining the SRM's two-phase windings with the prevailing power devices of an integrated power converter, eliminating the need for additional inductors and charging units. Simulations are run in MATLAB/Simulink, and simulation results are used to validate the control schemes for all modes.